Association between Maternal Mortality and Cesarean Section: Turkey Experience - Uzuncakmak, Cihangir (PLoS One, 2016)
BACKGROUND: To investigate the cesarean Section (C/S) rates and maternal mortality (MM) causes and its relation between 2002 and 2013. METHODS: Data were gathered from Turkish Ministry of Health and Istanbul Health Administration. The Annual Clinical Reports for 2002–2013 were reviewed and analyzed: C/Ss and maternal deaths in women who gave birth ≥20 weeks between January 1, 2002, and December 31, 2013, in any hospital in Turkey and Istanbul. RESULTS: The major causes of MM were hemorrhage (20%), hypertensive disorders (18.2%), embolism (10.3%), cardiovascular conditions (9%), infection (8.5%), and other causes (10.4%). Overall, the average annual CS delivery rate was 46.4% in Istanbul and 36.6% in Turkey. There was a significant increase in the CS rates in Istanbul and Turkey from 2008 to 2013 relative to those from 2002 to 2007 (p = 0.004). There was a statistically significant and inverse relationship (97.2%) between the MMR and CS rate from 2002 to 2013 in Turkey (p = 0.001). However, no significant relationship was detected between the MMR and CS rate from 2002 to 2013 in Istanbul (p > 0.05). There was a significant inverse correlation (66.3%) between the CS rate and peripartumhemorrhage in Turkey (p = 0.019) and there was a significant inverse correlation (66.5%) between the CS rate and peripartumhemorrhage(p = 0.018) in Istanbul between 2007 to 2013. There were no significant differences in ante-intrapartum haemorrhage bleeding (p > 0.05) or postpartum hemorrhage (p > 0.05) from 2007 to 2013. CONCLUSIONS: This study demonstrates that there was a inverse correlation between increased CS and maternal mortality rates during the previous decade in Turkey. Although cesarean rates increase excessively, it appears that improved health care facilities have a positive effect on MMRs in Turkey.